P147 Outcomes of pulmonary rehabilitation in severe asthma. (2nd December 2011) - Agbetile, J; Singh, S; Bradding, P; Pavord, I; Green, R
Abstract : Objectives: Structured physical training programmes are a key component of pulmonary rehabilitation (PR) and have consistently been shown to be of significant benefit to patients with COPD. It is unclear whether the application of similar principles provides similar health improvements in patients with severe asthma. We aimed to assess this by studying the effects of pulmonary rehabilitation in a group of patients with severe asthma and significant disability who have completed our standard 7 week PR programme. Methods: 111 patients with a physician diagnosis of severe asthma who have completed our standard PR programme were studied. Assessments including spirometry, chronic respiratory questionnaire (CRQ), hospital anxiety and depression scores (HAD) and incremental and endurance shuttle walk testing (ISWT, ESWT) were performed at baseline and completion to determine the effect of PR. Baseline demographic and spirometric data were compared with a larger population of patients with severe asthma attending our difficult asthma clinic (DAC). Results: Following rehabilitation, statistically significant improvements were seen in MRC dyspnoea score (mean (95% CI) improvement −0.35 (−0.13 to −0.57), p=0.003); HADS anxiety (−1.4 (−0.4 to −2.3), p=0.007); HADS depression (−1.2 (−0.2 to −2.2), p=0.026); CRQ dyspnoea (+0.72 (+0.33 to +1.1), p=0.001); CRQ fatigue (+0.92 (+0.65 to +1.2), p<0.001); CRQ Emotion (+0.64 (+0.36 to +0.92), p<0.001); CRQ mastery (+0.47 (+0.13 to +0.81), p=0.007); Incremental shuttle walk test (ISWT) (+63 m (49.5 to 76.5), p<0.001); and Endurance shuttle walk test (ESWT) (+339.7 m, (249.7 to 429.7), p<0.001). Interestingly however, patients with severe asthma who completed pulmonary rehabilitation were older (66 vs 48 yrs p<0.01), more likely to have smoked (69.5% vs 43.5%, p<0.01), and tended to have more severe fixed airflow obstruction (FEV1 % predicted 55.9 vs 71.9, p=0.28) than our DAC population. This may be because clinicians were more likely to refer patients with asthma who had a COPD-like phenotype or because patients with severe asthma were more likely to drop-out of the programme. Conclusion: Pulmonary rehabilitation may offer significant benefit to patients with severe asthma though further work is needed to identify the patients mostly likely to benefit and the optimum training required.